"Effing" the military: a political misunderstanding of management. Issue 4 (2nd October 2017) - White, Kenton
Abstract: The use of commercial business management techniques is widespread in all government departments, including the Ministry of Defence. This article examines the use of popular management techniques in the Armed Forces and argues that their application is misplaced. It looks at what the "effs" – "efficiency" and "effectiveness" – mean in the business world and to the Armed Forces. It compares the definitions both in business and the Armed Forces and finds that there are few, if any, situations where the same measurements can be applied. Whilst many management techniques are suited for business, the function of the Armed Forces and its output cannot be measured in the same way, complicated by the different metrics of "efficiency" in peace and in war. This difference may not be clearly understood by some politicians, or indeed by some senior military personnel. Using examples from some of the most popular management techniques such as "Lean" and "Agile" it is possible to see that their use might actually diminish the capabilities of the Armed Forces when it comes to performing their principal role – the use of force to achieve political objectives.